Multiscale modeling of dislocation patterns and simulation of nanoscale plasticity in body-centered cubic (BCC) single crystals. (September 2019) - Zhang, Lu-Wen; Xie, Yuxi; Lyu, Dandan; Li, Shaofan
Abstract: Understanding dislocation multiplication, interactions, and hence crystal plasticity has been a long-standing challenge of major scientific significance. Combining atomistic enriched constitutive law with continuum finite element formulation, we developed a multiscale framework to capture geometrically-compatible dislocation patterns in Body Centered Cubic (BCC) single crystals. This dislocation pattern dynamics framework was successfully applied to study crystal plasticity in Face Centered Cubic (FCC) crystals before, coined as the Multiscale Crystal Defect Dynamics (MCDD) method. Inheriting from MCDD method, we now established a multiscale dislocation pattern dynamics model for BCC crytals with the following novelties: (1) Comparing with molecular dynamics approach, MCDD can predict crystal plasticity in BCC crystals in a more efficient way and in larger scale; (2) MCDD can capture the geometrically-compatible dislocation pattern distribution and evolution in BCC crystals, and (3) MCDD can capture the size effect of crystal plasticity in single BCC crystals at nanoscale, or to simulate size-dependent plasticity in BCC single crystals. In particular, we have successfully simulated crystal plasticity in a BCC crystal at the sub-micron scale by using a serial computing code in a desktop environment.